2016
DOI: 10.1075/jicb.4.1.05pau
|View full text |Cite
|
Sign up to set email alerts
|

English-medium instruction in Sweden

Abstract: Yoxsimer Paulsrud, B. (2014). English-Medium Instruction in Sweden: Perspectives and practices in two upper secondary schools. Stockholm University, Dissertations in Language Education 3. ISBN: 978-91-7447-901-0. Written in English with a summary in Swedish.This thesis presents English-medium instruction (EMI) in the Swedish context, focusing on perspectives and practices in two schools. The research question is as follows: How and why is EMI offered, chosen, and practiced in the Swedish upper secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…Dalton-Puffer 2007;Lim Falk 2012;Yoximer Paulsrud 2014). This study shows an example of actual language use in such a situation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Dalton-Puffer 2007;Lim Falk 2012;Yoximer Paulsrud 2014). This study shows an example of actual language use in such a situation.…”
Section: Discussionmentioning
confidence: 93%
“…There is no declared policy regulating CLIL education in Sweden, neither in the national language policy, nor in the education policy (Lim Falk 2008;Sylvén 2013;Yoximer Paulsrud 2014). General guidelines as well as specific criteria and specified goals are also missing, and there is no systematic evaluation.…”
Section: Clil Education and The Swedish Contextmentioning
confidence: 96%
“…For instance, Nikula (2005) depicts a CLIL classroom (Finnish lower secondary school) where learners talk a great deal and see themselves and their teachers as equally proficient language users. Recently, Yoxsimer Paulsrud (2014) uses translanguaging as a lens to understand LA in Swedish CLIL contexts at academically oriented strands in upper secondary school and comes to the conclusion that it is a valuable tool for students in order for them to make use of all linguistic resources at hand. This is in line with what Smit (2010) and Moore and Dooly (2010) found among tertiary students engaged in hotel management education and a teacher training programme, respectively.…”
Section: Previous Research On Clilmentioning
confidence: 99%
“…However, while 'CLIL has a clear objective of furthering both content and language as declared in its title, EMI [English-medium instruction] does not (necessarily) have that objective' (Dearden, 2014, p. 4). Yoxsimer Paulsrud (2014) has concluded that EMI is more appropriate to describe such programmes in the Swedish context, where there are no explicit guidelines or teacher training for CLIL. These English-medium programmes generally lack the balance between content and language that CLIL offers in theory; English is simply the vehicle for content instruction.…”
Section: /2009 School Yearmentioning
confidence: 99%